Improving Patient Experience by Understanding Barriers and Incentives to Telehealth Adoption Among Physicians at a Large Academic Medical Center - Alessandro Luna MD, MBA; Taylor B Sewell MD, MBA (Journal of Patient Experience)
Patients benefit from and appreciate the option to use telehealth with their providers. Such patient expectations have therefore led to new questions about the factors that affect providers’ willingness to adopt telehealth as part of their clinical practice. We interviewed 19 physicians across four specialties with differential rates of telehealth use (Psychiatry, Anesthesiology, Physical Medicine & Rehabilitation [PM&R], and Ophthalmology) to discern the barriers and incentives to telehealth adoption among physicians. We then conducted a qualitative analysis of interview transcripts, following precepts of Directed Content Analysis. Conclusions drawn from matrix building and thematic analysis were verified with negative evidence searches and if-then tests. Robust investigations for outliers and rival explanations in responses were used to disconfirm findings. The results of this analysis revealed distinct barriers and incentives to telehealth adoption for the four specialties. Physicians in psychiatry and anesthesiology are refining the strengths and applications of telehealth based on the characteristic needs of their specialties. Physicians in PM&R and ophthalmology face additional barriers to acquiring physical exam data, leading them to use telehealth as a supplement to, rather than as a replacement for, core functions of patient care. The insights stemming from these barriers and incentives can be used to build thoughtful telehealth applications for physicians, allowing them to provide effective clinical care while also improving the patient experience.